2016
DOI: 10.1139/cjss-2015-0094
|View full text |Cite
|
Sign up to set email alerts
|

Woodchip biochar with or without synthetic fertilizers affects soil properties and available phosphorus in two alkaline, chernozemic soils

Abstract: Fertility enhancement with biochar application is well documented for tropical acidic soils; however, benefits of biochar coapplied with synthetic fertilizers (SFs) on soil fertility are not well documented, particularly for alkaline chernozems. We examined the short-term interactive effects of woodchip biochar amendment with fertilizers on selected soil properties, available phosphorus (P), and P fractions of two alkaline Chernozems from Manitoba. Treatments were (1) urea and monoammonium phosphate fertilizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 52 publications
0
31
1
Order By: Relevance
“…Furthermore, Zhai et al (2014) reported that maize straw biochar did not change the pH of an alkaline soil after 42 days of incubation. Moreover, Surani Chathurika et al (2016) reported that the coapplication of woodchip biochar (1-2% w/w) and urea and monoammonium phosphate fertilizers in two alkaline Chernozems did not change the soil pH to a greater extent than what was observed in the control condition (P > 0.05). However, Jin et al (2016) reported that applying 1.5% swine manure biochar raised the pH of neutral-to-alkaline soils by 0.5 and 0.6 pH units after 98 days of incubation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, Zhai et al (2014) reported that maize straw biochar did not change the pH of an alkaline soil after 42 days of incubation. Moreover, Surani Chathurika et al (2016) reported that the coapplication of woodchip biochar (1-2% w/w) and urea and monoammonium phosphate fertilizers in two alkaline Chernozems did not change the soil pH to a greater extent than what was observed in the control condition (P > 0.05). However, Jin et al (2016) reported that applying 1.5% swine manure biochar raised the pH of neutral-to-alkaline soils by 0.5 and 0.6 pH units after 98 days of incubation.…”
Section: Discussionmentioning
confidence: 97%
“…However, when all P fractionations were considered together, these changes appeared to be small. Chathurika et al (2016) studied the effects of woodchip biochar (1-2% w/w), urea and monoammonium phosphate fertilizer on Olsen P and its fractions in two alkaline Chernozems.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of biochar on P availability are variable: in some soils, biochar application has been observed to increase P availability, while in others, P availability was not affected or was observed to decrease, mainly due to increased P sorption (Chathurika et al, 2016). Biochar can induce changes in the soil ion exchange capacity.…”
Section: Crop Residues Manure and Biocharmentioning
confidence: 99%
“…Mean weight diameter is an important index of aggregate stability, calculated as the sum of the weighted mean diameters of all size The Journal of Agricultural Science classes, the weighting factor of each class being its proportion of the total sample weight. Both Ouyang et al (2013) and Chathurika et al (2016b) observed a significant increase in mean weight diameter with BC application to soils, suggesting the formation of more stable macro-aggregates, but this effect was only observed in sandy soils and not in clay soils. The mean weight diameter increased by twofold in a loamy sand with BC application at 20 g/kg, while there was no significant effect in a clay loam soil (Chathurika et al, 2016b).…”
Section: Amendment Effects On Soil Fertilitymentioning
confidence: 91%